Multimedialny charakter zajęć terapeutycznych = The multimedia nature of therapeutic activities - Nowicka, Ewa (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The main subject of the thesis is media and multimedia usage in therapy of specific reading and writing difficulties. There are lots of computer programmes which can be used to support the therapists work. It is very important to choose the best ones. The aim of the thesis is to present the most important features of properly prepared programmes.
Keywords: media; multimedia; technologie informacyjne; zajęcia terapeutyczne; specyficzne trudności w czytaniu i pisaniu; information technologies; pedagogical therapy; specific reading and writing difficulties